2019
DOI: 10.1021/acsomega.9b01806
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Nanoparticles for the Dispersion of Gas Hydrates in Slurry Flow

Abstract: Gas hydrates are crystals that can form in oil and gas production. Their agglomeration in flowlines may disrupt the normal production. One current strategy of hydrate management is to inject an anti-agglomerant, a type of low-dosage hydrate inhibitor that prevents hydrate agglomeration. Concerns in the use of these chemicals include their toxicity, cost, and environmental impacts. In this study, we exploited functionalized nanoparticles in place of anti-agglomerants to produce hydrate slurry, with the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
(101 reference statements)
0
14
0
Order By: Relevance
“…Sum and coworkers used this technique to measure the contact angle of silica nanoparticles functionalized with varying concentrations of n-octadecyltrimethoxysilane (ODTMS). 96 The contact radius d and the height of protrusion h of the nanoparticles at the water−n-decane interface (Figure 6B(a)) were measured by atomic force microscopy (AFM) and SEM (Figure 6B(b)), from which contact angles were calculated. Results showed that the contact angle increased with increasing concentration of n-octadecyltrimethoxysilane (Figure 6B(c)).…”
Section: ■ Hydrophobicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Sum and coworkers used this technique to measure the contact angle of silica nanoparticles functionalized with varying concentrations of n-octadecyltrimethoxysilane (ODTMS). 96 The contact radius d and the height of protrusion h of the nanoparticles at the water−n-decane interface (Figure 6B(a)) were measured by atomic force microscopy (AFM) and SEM (Figure 6B(b)), from which contact angles were calculated. Results showed that the contact angle increased with increasing concentration of n-octadecyltrimethoxysilane (Figure 6B(c)).…”
Section: ■ Hydrophobicitymentioning
confidence: 99%
“…Scale bars: 200 nm. (c) Measured protrusion heights h and contact angles θ. Reproduced from Zhang, X.; Gong, J.; Yang, X.; Slupe, B.; Jin, J.; Wu, N.; Sum, A. K. ACS Omega 2019 , 4 , 13496–13508 (ref ). Copyright 2019 American Chemical Society.…”
Section: Surface Chargementioning
confidence: 99%
See 1 more Smart Citation
“…In another aspect of industrial applications, hydrate formation needs to be hindered in the subsea oil-gas pipelines while promoted to efficiently store and transport gases under milder conditions. To achieve these targets, several thermodynamic inhibitors, antiagglomerates, and promoters have been proposed. One of these types is NPs. Solid NPs have been utilized to stabilize emulsions, the so-called Pickering emulsions, and thus to disperse gas hydrates in slurry flow to prevent gas hydrate agglomeration . At the same time, it is known that heterogeneous nucleation is generally more likely to occur than homogeneous nucleation, which means that NPs in solution might induce more rapid nucleation of gas hydrates.…”
Section: Introductionmentioning
confidence: 99%
“…The surfactant-based AAs have been studied but can cause environmental issues as a result of the toxicity nature and have drawbacks for recovering and reuse. Nowadays, the particle-type hydrate inhibitor has also been researched. Pickering emulsions are stabilized by nanoparticles with a hydrophobic surface, which suppressed the induction time of hydrate nucleation and prevented the agglomeration of hydrate particles . In addition, numerous studies have developed biosurfactants to develop novel AAs. ,, In our previous work, the hydrate formation characteristics in the presence of vitamin E succinate (vitamin ES) were investigated to evaluate its performance in dispersing hydrate particles in a liquid hydrocarbon stream.…”
Section: Introductionmentioning
confidence: 99%